2012
DOI: 10.1242/dev.073064
|View full text |Cite
|
Sign up to set email alerts
|

Temporal control of neural crest lineage generation by Wnt/β-catenin signaling

Abstract: SUMMARYWnt/-catenin signaling controls multiple steps of neural crest development, ranging from neural crest induction, lineage decisions, to differentiation. In mice, conditional -catenin inactivation in premigratory neural crest cells abolishes both sensory neuron and melanocyte formation. Intriguingly, the generation of melanocytes is also prevented by activation of -catenin in the premigratory neural crest, which promotes sensory neurogenesis at the expense of other neural crest derivatives. This raises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 44 publications
6
134
0
Order By: Relevance
“…Together with enhanced core factor expression, activation of the Notch/Wnt signalling pathways also increased the expression of NC markers in DPSCs. Both Notch and Wnt signals are associated with NC induction (Gazarian and Ramirez-Garcia, 2017;Hari et al, 2012;Leung et al, 2016;Rogers et al, 2012;Stuhlmiller and Garcia-Castro, 2012). Indeed, NC cells also express relatively high levels of core factors, which possibly relates to their ample capacity to generate very diverse cell lineages (Thomas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with enhanced core factor expression, activation of the Notch/Wnt signalling pathways also increased the expression of NC markers in DPSCs. Both Notch and Wnt signals are associated with NC induction (Gazarian and Ramirez-Garcia, 2017;Hari et al, 2012;Leung et al, 2016;Rogers et al, 2012;Stuhlmiller and Garcia-Castro, 2012). Indeed, NC cells also express relatively high levels of core factors, which possibly relates to their ample capacity to generate very diverse cell lineages (Thomas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Both pathways also play an important role in the emergence of the NC (Hari et al, 2012;Leung et al, 2016;Rogers et al, 2012;Stuhlmiller and Garcia-Castro, 2012). Dental stem cells present higher levels of core factors and Wnt/Notch activity compared to other mesenchymal stem cells in the adult body (Atari et al, 2012;Huang et al, 2009;Janebodin et al, 2011;Vasanthan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another study in mouse, contradicting zebrafish data shows that sustained ß-catenin activity in NC cells promoted the generation of sensory neurons, but had no effect on melanocyte formation (Lee et al, 2004). A later study using different Cre-lines to activate ß-catenin signaling at specific time points during NC development proved a temporal separation in generation of NC derivatives where sensory neurons are determined earlier than melanocytes (Hari et al, 2012). Thus, even after migration there seem to be a clear-cut time windows where canonical Wnt signaling exerts certain functions in the development of NC cells.…”
Section: Role Of Canonical Wnt Signaling In Post-induction Developmenmentioning
confidence: 94%
“…Canonical Wnt signaling has been associated with development of craniofacial structures and NC derivatives including melanocytes and sensory neural cells (Dorsky et al, 1998;Brault et al, 2001;Hari et al, 2002;Lee et al, 2004;Lewis et al, 2004;Hari et al, 2012). In zebrafish, overexpression of ß-catenin in premigratory NC cells has been shown to promote pigment cell formation at the expense of neurons and glia, while inhibition of Wnt signaling using a truncated form of Tcf3 or a dominant-negative Wnt1 caused an opposite effect promoting neuronal fate at the expense of pigment cells (Dorsky et al, 1998).…”
Section: Role Of Canonical Wnt Signaling In Post-induction Developmenmentioning
confidence: 99%
“…Wnt1-Cre has been shown to induce efficient recombination in neural crest cells (from which BC cells derive) and in the dorsal progenitor domain of spinal cord (Danielian et al, 1998;Jiang et al, 2000;Charron et al, 2003;Hari et al, 2012). By crossing the Wnt1-Cre line with the Z/EG reporter line, we confirmed that Wnt1-Cre-mediated recombination took place in neural crest cells, as indicated by the EGFP-positive dorsal root ganglia (DRG) and dorsal/ventral roots, as well as a dorsal progenitor domain and its derivatives in the spinal cord (Fig.…”
Section: Expression Of Cxcr4 In Radial Glia and Bc Cells During Spinamentioning
confidence: 99%